Методика оцінки професійної діяльності науково-педагогічних працівників та її програмна реалізація - Тугай, А. М.; Гойко, А. Ф.; Єлішевич, М. А.; Криштоф, С. Д. (Ways to Improve Construction Efficiency, 2012)
Assessment methodology disclosed professional researchers and teachers to promote the development of their creativity to design an efficient competitive environment in the team and staff of higher education.